Manajemen Inovasi SDM Dalam Era Globalisasi dan Teknologi 4.0: Perspektif dan Peluang - Ritonga, Rika Umbaiyani; Ary, Muhammad Hasan Asy; Putri, Yuliana; Suhairi, Suhairi (LPPM Universitas Labuhanbatu, 2023)
Globalization brings about changes in many areas, particularly in the areas of economy, politics, and technology. Globalization, though, also affects other fields, like human resource management (HRM). This desk study examines the role and influence of strategic management innovation on the preparation of human resources before entering the world of work and business in the midst of the 4.0 revolution in light of the emergence of a new paradigm that recognizes the role of humans as a fact that provides strategic direction and competitive advantage. Businesses and their human resources are dramatically impacted by technology improvements, creating more intense rivalry. Due to technology improvements, businesses must be more inventive and imaginative when it comes to strategic management. Large technology firms keep innovating inside their own structures. This includes their own unique innovation, processes, and goods. Companies that use open innovation strategies might use both internal and external sources of innovation. Alliance tactics may emerge in corporate initiatives to produce various ideas, and companies that pay more attention to innovation management to lessen rivalry are predicted to become more competitive.